Appositive Semantic Classification in Sumerian Cuneiform and the Implementation of iClassifier - Selz, Gebhard J. (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2022)
Sumerian, an agglutinative language of unknown affiliation, surfaced in mankind’s earliest written sources around 3300 BCE. It continued to play a salient role in the transmission of cuneiform cultures for more than three millennia, even after its disappearance as a vernacular (around 2000 BCE). From its beginnings, semantic classification played an important role in this initially pre-dominantly semasiographic-ideographic script. Here, such classifications are contrasted with and compared to the normalized ‘consolidated’ standard set of pre- and post-nominal classifiers – generally known as ‘determinatives’ – which function chiefly as sortal classifiers. It is further suggested here that the relationship between classifying nouns and classified nouns is best described in terms of nominal apposition. This paper further demonstrates how the relevant information was entered into the iClassifier system, specially designed for such comparisons in order to improve our understanding of how cuneiform classifiers mark their referents and to make them comparable with similar features in other scripts and languages. We will then briefly survey how the answers to queries in the iClassifier database may illuminate “the diverse mindsets of ancient Mesopotamia”.